Agta hunter–gatherer oral microbiomes are shaped by contact network structure. (23rd February 2023) - Musciotto, Federico; Dobon, Begoña; Greenacre, Michael; Mira, Alex; Chaudhary, Nikhil; Salali, Gul Deniz; Gerbault, Pascale; Schlaepfer, Rodolph; Astete, Leonora H.; Ngales, Marilyn; Gomez-Gardenes, Jesus; Latora, Vito; et al.
Abstract: Abstract: Here we investigate the effects of extensive sociality and mobility on the oral microbiome of 138 Agta hunter–gatherers from the Philippines. Our comparisons of microbiome composition showed that the Agta are more similar to Central African BaYaka hunter–gatherers than to neighbouring farmers. We also defined the Agta social microbiome as a set of 137 oral bacteria (only 7% of 1980 amplicon sequence variants) significantly influenced by social contact (quantified through wireless sensors of short-range interactions). We show that large interaction networks including strong links between close kin, spouses and even unrelated friends can significantly predict bacterial transmission networks across Agta camps. Finally, we show that more central individuals to social networks are also bacterial supersharers. We conclude that hunter–gatherer social microbiomes are predominantly pathogenic and were shaped by evolutionary tradeoffs between extensive sociality and disease spread.